2017
DOI: 10.5487/tr.2017.33.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Peripheral Ameloblastic Odontoma in a Male Sprague-Dawley Rat

Abstract: Peripheral ameloblastic odontoma is a rare variant of odontogenic tumor occurring in the extraosseous region. The present report describes a spontaneous tumor in male Sprague-Dawley (SD) rats. The clinically confirmed nodule in the right mandibular region was first observed when the rat was 42 weeks and remained until the terminal sacrifice date when the animal was 48 weeks of age. At necropsy, a well demarcated nodule, approximately 2.5 × 2.0 × 2.0 cm, protruded from the ventral area of the right mandible. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Our review of 2 published cases using the term ameloblastic odontoma revealed a suspected odontoameloblastoma in a llama 24 and an ameloblastic fibro-odontoma in a rat. 15 The histologic features of an ameloblastic odontoma associated with the mandibular incisor teeth of a llama described in the paper were proliferating ameloblasts in the presence of dentin. These are features suggestive of an odontoameloblastoma; however, there are no histologic images available upon which to conclusively review the diagnosis.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Our review of 2 published cases using the term ameloblastic odontoma revealed a suspected odontoameloblastoma in a llama 24 and an ameloblastic fibro-odontoma in a rat. 15 The histologic features of an ameloblastic odontoma associated with the mandibular incisor teeth of a llama described in the paper were proliferating ameloblasts in the presence of dentin. These are features suggestive of an odontoameloblastoma; however, there are no histologic images available upon which to conclusively review the diagnosis.…”
mentioning
confidence: 87%
“…10,17 A consensus regarding this specific issue within the nomenclature has not been reached. The term ameloblastic odontoma is still in use, 15,24 but is described as obsolete elsewhere. 2,5 To complicate matters further, ameloblastic odontoma is frequently considered to be a synonym of odontoameloblastoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation